1991
DOI: 10.1007/bf00051672
|View full text |Cite
|
Sign up to set email alerts
|

Vegetables, fruit, and cancer. I. Epidemiology

Abstract: The epidemiologic literature on the relationship between vegetable and fruit consumption and human cancer at a variety of sites is reviewed systematically. A total of 13 ecologic studies, nine cohort studies, and 115 case-control studies are included. Cancer of all sites, cancers of lung, breast, colon, rectum, esophagus, larynx, oral cavity and pharynx, stomach, pancreas, prostate, bladder, ovary, endometrium, cervix, and thyroid, as well as mesothelioma and gestational trophoblastic disease, are considered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
437
3
10

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,112 publications
(457 citation statements)
references
References 123 publications
7
437
3
10
Order By: Relevance
“…High intakes of fruits and vegetables have been associated with reduced risks of many cancers, 22 including breast cancer, [23][24][25][26][27] as well as of benign breast disease 26,[28][29][30] ; but some studies 26,[31][32][33] have shown either only a moderate, or no reduction in risk of breast cancer in association with these foods. A meta-analysis of 14 casecontrol studies and 3 cohort studies showed a reduced risk of breast cancer in relation to vegetable consumption, but with significant heterogeneity among studies, and only a weak, non-significant, association with fruit intake.…”
Section: Discussionmentioning
confidence: 99%
“…High intakes of fruits and vegetables have been associated with reduced risks of many cancers, 22 including breast cancer, [23][24][25][26][27] as well as of benign breast disease 26,[28][29][30] ; but some studies 26,[31][32][33] have shown either only a moderate, or no reduction in risk of breast cancer in association with these foods. A meta-analysis of 14 casecontrol studies and 3 cohort studies showed a reduced risk of breast cancer in relation to vegetable consumption, but with significant heterogeneity among studies, and only a weak, non-significant, association with fruit intake.…”
Section: Discussionmentioning
confidence: 99%
“…11,21 With regard to fruit intake, the small number of smokers is likely to have affected the power of our study to detect a significant relationship; the odds ratio for the highest tertile does suggest the possibility of a substantial reduction in risk that is consistent with results for smokers in other studies. 11,13 Interestingly, recent results from a prospective investigation (the Nurses' Health Study) show a significant reduction in risk with the highest quintile of intake for total vegetables, but not fruit, among current smokers, whereas among never smokers, the highest tertile of fruit intake had a significant protective effect. 22 Among lifetime nonsmokers, place of birth was the demographic variable most strongly associated with lung cancer risk; non-smoking women who were born in China experienced a more than twofold increase in risk compared to local-born women.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recent studies support an effect of total fruit and vegetable intake rather than of individual micronutrients, 11 with the evidence being most consistent for Brassica vegetables, which are rich in isothiocyanates, potent inhibitors of NNK carcinogenesis. 12 Accordingly, the trend has been toward a stronger effect of vegetables in smokers, 13 possibly because of specific agents with anticarcinogenic properties against tobaccorelated cancers. Several studies have reported inverse associations between vegetable intake and lung cancer risk among smokers or exsmokers but these associations were absent among women who have never smoked.…”
mentioning
confidence: 99%
“…dietary habits, may largely determine each individual's tumor risk. Diets rich in cruciferous vegetables, such as Brussels sprouts (Brassica oleraceae), are associated with a lower risk (2). The anticarcinogenic properties of cruciferous vegetables have been mainly attributed to the degradation products of glucosinolates, e.g.…”
Section: Introductionmentioning
confidence: 99%